Strengthening Proposal Writing Skills through Research Grants and PKM Bima Workshop - Ahmad Yani T; Urai Salam; Venny Karolina; Carla Querioz; Fithra Ramadian; Firda Islamaya Farhan; Ayu Chandra Kartika; Diajeng Ramadhani (I-Com: Indonesian Community Journal, 2024)
Training on Research Grant Proposal Writing and PKM at FKIP UNTAN aims to improve the ability of lecturers to design superior and quality research proposals. This activity was carried out in three stages, namely preparation, implementation, evaluation and reporting. The implementation stage consists of two methods, namely lecture methods, interactive discussions and case studies of examples of proposals that pass funding. The discussion revealed strategies for writing competitive proposals, obstacles in data collection and proposal preparation. The active involvement of the participants showed high enthusiasm, with more than half of the participants planning to apply for Bima Grants next year, supported by the materials from this training. The event not only provided in-depth insights into quality proposal writing, but also emphasized the importance of concrete steps to achieve research goals and contributions to society. The training has helped improve participants' understanding and readiness to develop more competitive grant proposals.